IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH GAME: A CASE STUDY OF NON-FORMAL STUDENTS OF PKBM DARUSSA’ADAH PALANGKA RAYA - Haryani, Tutik (JURNAL SOCIOPOLITICO, 2024)
The purpose of this study was to use the game to improve vocabulary mastery. The purpose of the game is to test whether it can help students become more proficient with vocabulary and to determine how well games work in the classroom. Ten of PKBM Darussa’adah students and one English teacher participated in this study. The information was gathered by interviewing one teacher and distributing questionnaires to students. This study used the qualitative descriptive method to analyze the data. The findings of this study demonstrate how well games may be incorporated into the teaching and learning process by boosting students' interest and motivation. In fact, it becomes a useful strategy for teacher to help pupils become more proficient in terminology.